The Guilt and Conscience. An Ethical Commentary to the Epilogue of Dostoyevsky’s Crime and Punishment - Wierzbicki, Alfred Marek (Filozofia Chrześcijańska, 2012)
Dostoyevsky’s famous novel Crime and Punishment can be interpreted as an argument with Nietzsche’s view on the genealogy of conscience. While Nietzsche believes that conscience is a product of a disease and inhibits the will to power, Dostoevsky shows the situation of crossing the border as a source of moral illness and self-destruction of the human person. Crime and Punishment, as well as Dostoevsky’s novel Demons and The Trial of F. Kafka, also criticize modern and postmodern society, in which there is a strong trend, stimulated by psychoanalysis, to liberate people from guilt. With reference to Martin Buber’s views, the author of the article formulates a thesis on the ontological nature of guilt, treating its confession as a necessary act of self-enlightenment in conscience.Examining the structure of conscience in the context of guilt, a deeper level must be indicated, called synderesis in the scholastic tradition. Considering the elements of experience present in the experience of conscience, the author criticizes the intellectualist interpretation of synderesis. He takes into account the deep level of understanding of conscience in the category of heart made by D. v. Hildebrand and the anamnesis category of J. Ratzinger.